2010
DOI: 10.1007/s00264-010-1105-6
|View full text |Cite
|
Sign up to set email alerts
|

The management of nonunion and delayed union of patella fractures: a systematic review of the literature

Abstract: Nonunion and delayed union of patella fractures are rare conditions that are fraught with challenges. There exists limited evidence in the literature to guide the clinician in the management of these complications. Therefore, the purpose of this study was to perform a systematic review of the available evidence on the management of nonunion and delayed union of patella fractures. A total of five publications which met our criteria were identified and formed the basis of this study. The decision making in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 8 publications
1
32
0
5
Order By: Relevance
“…With gravity providing the counter force in the patellar traction, there is never a chance of patellar tendon rupture. Nathan et al 9. systematically reviewed five articles in their recent publication and found that surgical management in the form of TBW is the best management for high demand patients.…”
Section: Discussionmentioning
confidence: 99%
“…With gravity providing the counter force in the patellar traction, there is never a chance of patellar tendon rupture. Nathan et al 9. systematically reviewed five articles in their recent publication and found that surgical management in the form of TBW is the best management for high demand patients.…”
Section: Discussionmentioning
confidence: 99%
“…Merdiven çıkmada zorlanma ve diz hareketlerinde kısıtlılık da bildirilmiştir. [8] İhmal edilmiş kırıklarda belirgin kaynamama ve kırık hattında ayrış-ma var ise, hasta ekstansör mekanizmanın çalışmama-sına bağlı gelişen bulgular ile başvurur. [7] Patella kırıklarında kaynamama, erkeklerde kadınla-ra oranla daha yüksek oranda görülmektedir; ortalama görülme yaşı 38'dir.…”
Section: Kli̇ni̇k Bulgularunclassified
“…[6] Kaynamama ve gecikmiş kaynama, cerrahi tedavi edilen tüm kı-rıkların %2,7-12,5'inde görülür. [8] Tedavi görmemiş, belirgin ayrışmış, ekstansör mekanizması çalışmayan hastalarda kaynamama tanısı kolaylıkla konulurken, konservatif veya cerrahi tedavi görmüş hastalara ne kadar sürede iyileşme beklendiği ve ne zaman kaynama gecikmesi tanısı konulacağı konusunda, insidansın çok düşük olması nedeniyle, kesin bir görüş birliği yoktur. Özellikle, cerrahi tedavi edilmiş hastalarda kaynamama ve implant yetmezliği ayrımını yapmak oldukça güçtür.…”
unclassified
See 1 more Smart Citation
“…Patellar fractures must follow principles of articular fracture management, which involves anatomic reduction, stable fixation, and early motion. In cases of nonunions, attempts to reestablish a complete range of motion may involve internal fixation or even partial or total resection of this bone [73]. There is a paucity of data depicting the use of biological therapies on enhancing patellar bone healing.…”
Section: Patellamentioning
confidence: 99%